Twelve high yielding and nutritious lines of irrigated lowland rice breeding lines identified - CGIAR Research Program on Rice (2021)
Forty-five entries were tested in multi-location trials at two sites in Senegal and one site in Cote d'Ivoire under irrigated lowland conditions in 2020. Based on superiority over local checks and low chalkiness, seven lines were selected for testing in six African countries.